The importance of controlling and treating systemic arterial hypertension in the family health strategy (Research, Society and Development, 2023)
Systemic arterial hypertension remains one of the biggest public health challenges worldwide. The investment of professional teams, health centers and all countries in the fight against SAH is a way to seek to improve quality of life and combat premature death. Based on the primary analysis, the aim of this review is to point out the importance of family health strategies in the treatment and control of systemic arterial hypertension. This is a narrative bibliographic review. The results show that hypertension continues to be one of the greatest public health challenges in Brazil and in the world, and the most important factor in health control and promotion through primary health care. The implementation of the family health strategy has impacted on the control of chronic diseases such as hypertension, but we still have many problems in the effective performance of the team, the most prominent of which is the lack of planning and education in Health. It concludes the importance of maintaining and expanding public health policies close to populations. This can be achieved much more than provides the minimum conditions of treatment, but also through advocacy and education of the population so that it can seek better conditions.